Outcomes after surgical treatment of acetabular fractures: a review - Ziran, Navid (Patient Saf Surg, 2019)
Acetabular fractures are fractures that extend into the hip joint and pose a challenge for orthopaedic trauma surgeons. The first known descriptions of surgical fixation of acetabular fractures were case reports in 1943. In 1964, Robert Judet, Jean Judet, and Émile Letournel published a landmark article describing a classification system and surgical approaches to treat acetabular fractures. These teachings had a significant effect on clinical outcomes after surgical fixation of acetabular fractures. In 1980, Letournel demonstrated 80% good-to-excellent results in 492 hips, and in 2012, Joel Matta demonstrated 79% survivorship in 816 patients follow surgical acetabular fixation. Both Letournel and Matta have definitively shown that anatomic reduction of the fracture is the most influential factor predictive of clinical outcome. The intent of this review is to summarize the salient factors affecting clinical outcomes after surgical treatment of acetabular fractures.